Fade into you - Darling, Nikki, 1980- (Feminist Press, 2018)
A portrait of a young girl in the glorious wasteland of 1990s Los Angeles, Fade Into You recalls the hormonal haze and urgency of adolescence. High school junior Nikki Darling alternates between cutting class and getting high, falling into drugs, crushes, and counterculture to figure out how she fits into the world. Running increasingly wild with other angst-ridden outcasts, she pushes herself to the edge only to find herself trapped in the cyclical violence of growing up female. Written in dreamy, subterranean prose, this novel captures the reckless defiance and fragility of girlhood.